PENDETEKSIAN PERILAKU HERDING PADA PASAR SAHAM INDONESIA DAN ASIA PASIFIK (Detection of Herding Behavior on Indonesia and Asia Pacific Stock Market) - . Gunawan; Hari Wijayanto; Noer Azam Achsani; La Ode Abdul Rahman (FORUM STATISTIKA DAN KOMPUTASI, 2011)
Herding Behavior is an irrational investor behavior, because investors do not make investment decisions based on economic fundamentals of risky assets, but based on others investor in the same condition, or following market consensus. Herding behavior indications can be seen from relation between dispersion of stock return (Cross Sectional Absolute Deviation, CSAD) and market portfolio return. If herding behavior exist, CSAD increases lower than increase of market portfolio return moreover, CSAD will decrease even though market portfolio return increases. Herding behavior in stock market can trigger mislead in stock pricing because is bias among investors in analyzing risk and return. To understand relationship between CSAD and market portfolio return in some conditions, Quantil regression is used. Result gained from this research is that in Indonesian and global Asia Pacific stock market, herding behavior occurs in a market stress condition, whereas in normal condition or in condition of very high stock return, investor behavior tends to be more rational. Keywords : herd behavior, Quanrtile regression, CSAD